2018
DOI: 10.1039/c8ta03991g
|View full text |Cite
|
Sign up to set email alerts
|

Porous organic materials with ultra-small pores and sulfonic functionality for xenon capture with exceptional selectivity

Abstract: Exceptional selectivity and high adsorption capacity for xenon have been realized by simultaneously introducing plenty of narrow pores and engineering the pore surface with sulfonic functionality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(23 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…For example, MOFs with high surface area (e.g., IRMOFs, UiO-66) and polar functional groups (e.g., IRMOF-X, UiO-66-X, X = Cl, F, Br, I, NH 2 , etc.) have shown high Xe uptake, but weak gas–adsorbent interactions in these cases have resulted in low gas selectivity. Additionally, MOFs with accessible, highly polarizable open metal sites (e.g., MOF-74 series, HKUST) have also been evaluated for noble gas separation because of their stronger affinity to Xe than Kr. , A number of reports suggest that optimal pore size comparable to the kinetic diameter of Xe is a key factor for high capacity and selectivity. Among many MOF materials tested for Xe/Kr separation, ,,, the highest Xe/Kr selectivity has been achieved recently by CROFOUR-1-Ni systems, reaching a value of 22 at 1.0 bar and 298 K …”
Section: Introductionmentioning
confidence: 99%
“…For example, MOFs with high surface area (e.g., IRMOFs, UiO-66) and polar functional groups (e.g., IRMOF-X, UiO-66-X, X = Cl, F, Br, I, NH 2 , etc.) have shown high Xe uptake, but weak gas–adsorbent interactions in these cases have resulted in low gas selectivity. Additionally, MOFs with accessible, highly polarizable open metal sites (e.g., MOF-74 series, HKUST) have also been evaluated for noble gas separation because of their stronger affinity to Xe than Kr. , A number of reports suggest that optimal pore size comparable to the kinetic diameter of Xe is a key factor for high capacity and selectivity. Among many MOF materials tested for Xe/Kr separation, ,,, the highest Xe/Kr selectivity has been achieved recently by CROFOUR-1-Ni systems, reaching a value of 22 at 1.0 bar and 298 K …”
Section: Introductionmentioning
confidence: 99%
“…18,24 Xiong and Wang also investigated the xenon adsorption behaviors on ultramicroporous MOFs deeply, and reported that Zn-(tmz) 2 (4.3 Å), MOF-Cu-H (4-6 Å) and Zn(ox) 0.5 (trz) (4 Å) all had good adsorption properties that the xenon uptakes were above 2.5 mmol g À1 and Xe/Kr selectivity was up to 15.5 at 298 K and 1 bar. [25][26][27] The latest research found that the Xe/Kr adsorption selectivity of PAF-45S with a pore size of 5.2 Å was about 16.7, 28 while the Cosquarate frameworks with 4 Å pores and NbOFFIVE-2-Cu-i with 5 Å pores were as high as 54.1 and 43, respectively. 29,30 More importantly, the Co-squarate framework is especially applicable for trace xenon capture from air owing to the high Henry constant of 192 mmol g À1 bar À1 .…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25] Furthermore, studies on the selectivity of Xe/Kr with MOFs under irradiation conditions have emerged with the development of nuclear energy. [26][27][28][29][30][31][32][33][34][35][36][37][38][39] Thallapally et al proposed a concept of a two-bed radioactive off-gas treatment with Ni/DOBDC and FMOF-Cu. 40,41 Sameh et al synthesized a SIFSIX-3-M (Cu, Zn, Co, Fe, Ni) series.…”
Section: Introductionmentioning
confidence: 99%